Correction: Encapsulating bacteria in alginate-based electrospun nanofibers. (24th February 2022) - Diep, Emily; Schiffman, Jessica D.
Abstract : Correction for 'Encapsulating bacteria in alginate-based electrospun nanofibers' by Emily Diep et al., Biomater. Sci., 2021, 9, 4364–4373, DOI: ; 10.1039/D0BM02205E .